2017
DOI: 10.1080/08958378.2017.1357774
|View full text |Cite
|
Sign up to set email alerts
|

The role of the lectin-like oxLDL receptor (LOX-1) in traffic-generated air pollution exposure-mediated alteration of the brain microvasculature in Apolipoprotein (Apo) E knockout mice

Abstract: Recent studies have shown a strong correlation between air pollution-exposure and detrimental outcomes in the central nervous system, including alterations in blood brain barrier (BBB) integrity, neuroinflammation, and neurodegeneration. However, the mechanisms mediating these pathologies have not yet been fully elucidated. We have previously reported that exposure to traffic-generated air pollution results in increased circulating oxidized low-density lipoprotein (oxLDL), associated with alterations in BBB in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 66 publications
(115 reference statements)
4
18
0
Order By: Relevance
“…Three mo-old male C57BL/6 mice were placed on either normal mouse chow or a HF diet (TD88137 Custom Research Diet, Harlan Teklad, Madison, WI; 21.2% fat content by weight, 1.5g/kg cholesterol content) beginning 30 days prior to initiation of exposure. Mice were randomly grouped to be exposed by whole-body inhalation to a mixture of whole gasoline engine exhaust and diesel engine exhaust (MVE: 30 µg PM/m 3 gasoline engine emissions + 70 µg PM/m 3 diesel engine) or filtered-air (controls) for 6 h/d, 7 d/wk, for a period of 30 d. MVE was created by combining exhaust from a 1996 GM gasoline engine and a Yanmar diesel generator system, and exposures chemistries and PM characterized, as previously reported (McDonald et al, 2004; McDonald et al, 2008; Lund et al, 2011; Oppenheim et al, 2013; Mumaw et al, 2016; Lucero et al, 2017.). Particle size distribution was measured with a Fast Mobility Particle Sizer (FMPS, TSI, St. Paul, MN) for the ∼10–500 nm size range and an Aerodynamic Particle Sizer (TSI, St Paul, MN) to measure the 0.5–20 µm size range.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three mo-old male C57BL/6 mice were placed on either normal mouse chow or a HF diet (TD88137 Custom Research Diet, Harlan Teklad, Madison, WI; 21.2% fat content by weight, 1.5g/kg cholesterol content) beginning 30 days prior to initiation of exposure. Mice were randomly grouped to be exposed by whole-body inhalation to a mixture of whole gasoline engine exhaust and diesel engine exhaust (MVE: 30 µg PM/m 3 gasoline engine emissions + 70 µg PM/m 3 diesel engine) or filtered-air (controls) for 6 h/d, 7 d/wk, for a period of 30 d. MVE was created by combining exhaust from a 1996 GM gasoline engine and a Yanmar diesel generator system, and exposures chemistries and PM characterized, as previously reported (McDonald et al, 2004; McDonald et al, 2008; Lund et al, 2011; Oppenheim et al, 2013; Mumaw et al, 2016; Lucero et al, 2017.). Particle size distribution was measured with a Fast Mobility Particle Sizer (FMPS, TSI, St. Paul, MN) for the ∼10–500 nm size range and an Aerodynamic Particle Sizer (TSI, St Paul, MN) to measure the 0.5–20 µm size range.…”
Section: Methodsmentioning
confidence: 99%
“…increase ox-LDL) (Ikeda et al, 1995), higher levels of which are associated with progression of cardiovascular disease, atherosclerotic plaque growth, as well as poorer prognostic outcome in stroke (Ishigaki et al, 2009). Additionally, our laboratory has previously reported that inhalation exposure to a mixture of gasoline and diesel engine exhaust (MVE) resulted in increased circulating ox-LDL in atherosclerotic Apolipoprotein (Apo)E −/− mice, which was associated with increased expression of microvascular LOX-1 and ROS (Lund et al, 2011; Lucero et al, 2017). Furthermore, exposure to air pollution has also been associated with altered BBB integrity and permeability in both laboratory studies and human exposures (Oppenheim et al, 2013; Calderón-Garcidueñas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Localization of particulate matter in the CNS has been demonstrated after high dose exposures but has only been experimentally linked to neuroinflammation and pathology in an associative manner. However, indirect inflammatory effects due to pulmonary damage may be carried into circulation, as demonstrated mechanistically in several recent studies of both particulate and gaseous inhaled toxicants (Aragon et al, 2017;Channell et al, 2012;Lucero et al, 2017;Robertson et al, 2013;Schisler et al, 2015). For exposures to lower doses of inhaled toxicants, this may be the likely mechanism of neuroinflammatory effects.…”
mentioning
confidence: 99%